2009
DOI: 10.1200/jco.2008.21.4643
|View full text |Cite
|
Sign up to set email alerts
|

Prevailing Ethical Dilemmas in Terminal Care for Patients With Cancer in Taiwan

Abstract: The enactment of the Natural Death Act in Taiwan would contribute to improving the quality of end-of-life care, which suggests that this kind of law should be adopted in other countries. Educating cancer care professionals in building positive beliefs toward the act is strongly encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 32 publications
2
47
1
Order By: Relevance
“…In her opinion, the failure of medical professionals to accede to her request was tantamount to reckless abandonment and medical failure (Oh et al 2004, Oh et al 2007, Van der Riet et al 2008, Chiu et al 2009, del Rio et al 2011. She argued that food and drink was part of basic care and demonstrates her continued support of him even at the bleakest of times.…”
Section: Comfort Hope and Balancing Competing Goals Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…In her opinion, the failure of medical professionals to accede to her request was tantamount to reckless abandonment and medical failure (Oh et al 2004, Oh et al 2007, Van der Riet et al 2008, Chiu et al 2009, del Rio et al 2011. She argued that food and drink was part of basic care and demonstrates her continued support of him even at the bleakest of times.…”
Section: Comfort Hope and Balancing Competing Goals Of Carementioning
confidence: 99%
“…In Madam W's case allowing the insertion of NG tube enabled the family time to accept her poor prognosis and time to come to terms with their impending loss. Importantly for them, it allowed them a chance participate in their mother's patient's physical care, continue show their affection towards her and redress their own beliefs about the disease process and shift primary focus away from food (Slomka 2003, Goh 2007, Goh 2008, Chiu et al 2009.…”
Section: Filial Pietymentioning
confidence: 99%
“…Legal immunity for not resuscitating imminently dying patients was provided to healthcare professionals after the Taiwanese lawmakers established the Hospice-Palliative Care Act in 2000. 22 Decisions about DNR have to be made by patients, or surrogate decision-makers (usually the family members) for incompetent patients, in consultation with their physicians. Several studies conducted in Taiwan have reported that older age, 2325 unmarried, 24 and longer stay in an ICU 25 were associated with a DNR decision.…”
Section: Introductionmentioning
confidence: 99%
“…Such treatment decisions therefore involve ethical, emotional, and cultural challenges for health professionals. 14 Previous study that focused on nurses in general wards showed that nurses had complex emotions about ANH for patients with terminal cancer. They believed that providing ANH resulted in more harm than benefit, but their attitudes and behavioral intentions favored the provision of such care.…”
mentioning
confidence: 99%